Isotherapy and Artistic and Creative Habilitation of Preschool Children with Autism Spectrum Disorders - Forseeva, I.V. (Bulletin of Practical Psychology of Education, 2020)
The article presents the experience and results of the work of the compensatory type Kindergarten No. 7 teachers with children with autism spectrum disorders on the use of art-pedagogical technologies in practice. 97 preschoolers with disabilities are brought up in this Kindergarten, and 15 people have autism spectrum disorders. All kindergarten preschool children with autism spectrum disorders are integrated into groups of compensating orientation for children with severe speech disorders, taking into account age characteristics. Education and training of preschool children in this category is complicated by violations of their social interaction, scattered attention, backwardness of large and small motor skills, increased excitability and exhaustion, impulsivity and short temper. They do not know how to obey group rules for a long time, listen to and follow instructions, bring the work started to the end, and achieve a certain result. In working with preschoolers with autism spectrum disorders, teachers see prospects for correcting and compensating for violations in the development of artistic and creative activities. The tasks that are solved in an educational organization using methods of artistic and creative habilitation are to develop the child’s personality; develop and correct emotional and volitional processes, reduce fears through isotherapy; create conditions for free experimentation with artistic materials and tools; create an emotional atmosphere that will engage children with autism spectrum disorders in artistic activities. Teachers in their work rely on scientific theories that confirm the validity of the practice of isotherapy, on the results of scientific and applied research in this area, as a result of artistic and creative habilitation, contact was established with every child with autism spectrum disorders (100%). Children have a desire to engage in artistic and creative activities (100%), many began to respond adequately emotionally in various situations of interaction with adults and peers (65%), show empathy for other children (40%), decreased anxiety and fears in new situations of interaction. В статье представлен опыт и результаты работы педагогов МБДОУ «Детский сад № 7 компенсирующего вида» с детьми, имеющими расстройства аутистического спектра, по использованию на практике арт-педагогических технологий. В ДОУ воспитываются 97 дошкольников с ограниченными возможностями здоровья, 15 человек имеют расстройства аутистического спектра. Все воспитанники детского сада с расстройствами аутистического спектра интегрированы в группы компенсирующей направленности для детей с тяжелыми нарушениями речи с учетом возрастных особенностей. Воспитание и обучение дошкольников данной категории осложняют нарушения у них социального взаимодействия, рассеянное внимание, неразвитость крупной и мелкой моторики, повышенная возбудимость и истощаемость, импульсивность и вспыльчивость. Они не умеют длительное время подчиняться групповым правилам, выслушивать и выполнять инструкции, доводить начатое дело до конца, добиваться определенного результата. В работе с дошкольниками с расстройствами аутистического спектра педагоги видят перспективы коррекции и компенсации нарушений в развитии средствами художественно-творческой деятельности. Задачи, которые решаются в образовательной организации с помощью методов художественно-творческой абилитации, заключаются в развитии личности ребенка; развитии и коррекции эмоционально-волевых процессов, снижении страхов посредством изотерапии; создании условий для свободного экспериментирования с художественными материалами и инструментами; создании эмоциональной атмосферы, которая будет увлекать детей с расстройствами аутистического спектра художественной деятельностью. Педагоги в своей работе опираются на научные теории, подтверждающие обоснованность применения практики изотерапии, на результаты научных и прикладных исследований в этой области, В результате художественно-творческой абилитации был установлен контакт с каждым ребенком с расстройствами аутистического спектра (100%). У детей появилось желание заниматься художественно-творческой деятельностью (100%), многие стали адекватно эмоционально реагировать в различных ситуациях взаимодействия с взрослыми и сверстниками (65%), проявлять сочувствие к другим детям (40%), снизились тревожность и страхи в новых ситуациях взаимодействия.